2018
DOI: 10.1016/j.cgh.2017.10.001
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Staging Systems for Hepatocellular Carcinoma in a Multicenter US Cohort

Abstract: H epatocellular carcinoma (HCC) staging guides patient prognosis and treatment allocation; however, there is no universally accepted staging system for HCC. The most widely endorsed staging system is the Barcelona Clinic Liver Cancer (BCLC) system, which incorporates tumor burden, functional status, and liver function. 1 We aimed to compare the discriminant ability of several staging systems for HCC in a geographically diverse multicenter US cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Thus, Asians with HCC could particularly benefit from HKLC, since it indicates more aggressive curative treatments than the BCLC. However, like many previous studies, the present study involved a Western sample[8,23,27,28]. Only 6% of the cases were HBV related, and most patients had chronic HCV infection.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, Asians with HCC could particularly benefit from HKLC, since it indicates more aggressive curative treatments than the BCLC. However, like many previous studies, the present study involved a Western sample[8,23,27,28]. Only 6% of the cases were HBV related, and most patients had chronic HCV infection.…”
Section: Discussionmentioning
confidence: 96%
“…Biopsy for the diagnosis of HCC is not currently routinely recommended by guidelines due to the risk of tumour seeding, bleeding and sampling error 6 . Similarly, the only validated non‐invasive prognostic markers for HCC are tumour staging and alpha‐fetoprotein levels, both of which have significant limitations in approximating tumour biology 7,8 . This is particularly important in light of recent data showing variation in tumour growth patterns, with one‐fourth of HCC having rapid growth patterns and over one‐third having indolent growth 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the current staging systems still need improvement, for example, incorporating new risk factors for a better stratification of postoperative outcome. In fact, traditional staging systems mainly consist of pathological factors, like tumor size and vascular invasion, while tremendous information in preoperative computed tomography (CT) or magnetic resonance imaging (MRI) reflecting tissue intrinsic characters and heterogeneity [ 5 8 ] remains untapped. Recently, it has been reported that various imaging features were associated with pathological features and prognosis of the tumor and complementary to current staging systems, like rectal cancer and bladder cancer [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%